Biological and clinical response to desmopressin (DDAVP) in a retrospective cohort study of children with low von Willebrand factor levels and bleeding history - Sánchez Luceros, Analía Gabriela (2010)
The diagnosis and management of von Willebrand disease (VWD) in paediatrics is challenging. Our aim was to review patient's characteristics related to biological and clinical response to DDAVP in children with low von Willebrand factor (VWF) levels and bleeding history from a single institution. We included a retrospective cohort of 221 children (median age 11 years; 137 females): 27 type 1 (VWF levels within 15-30 IU dL-1) and 194 possible type 1 (VWF levels within 31-49 IU dL-1). The DDAVP infusion-test was performed in 214/221 children, 93.4% of whom showed good response. Patients with type 1 were at higher risk of DDAVP-test failure: 9/26 (34.6%) vs. 18/188 (9.6%) with possible type 1 (RR 3.44, 1.75-6.79; p= 0.002, Fisher's exact test). In 68 children, the clinical response to DDAVP was evaluated 87 times: i) to stop bleeding: menorrhagia (13), mucocutaneous (12), haemarthrosis (1); and ii) to prevent surgical bleeding: adenotonsillectomy (17), major (15) and minor surgery (10); and dental procedures (19). No major adverse events or bleeding were observed. The treatment was effective with one single dose of DDAVP in almost all patients, without antifibrinolytic or local therapy, except in a girl with severe haemorrhage during menarche who required replacement therapy. In conclusion, patients with VWD type 1 were at higher risk of no response to DDAVP infusion-test. In this series, one dose of DDAVP proved effective and safe for children with VWD. Since this is a safe, effective and affordable therapy, we consider that a wider use should be promoted, especially in developing countries.